Isolation and Identification of Pigment-Producing Endophytic Fungi from the Amazonian Species Fridericia chica - Dorothy Ívila de Melo Pereira; Raiana Silveira Gurgel; Anne Terezinha Fernandes de Souza; Rosiane Rodrigues Matias; Lucas de Souza Falcão; Francisco Celio Maia Chaves; Gilvan Ferreira da Silva; José Gregorio Martínez; Rudi Emerson de Lima Procópio; Cleiton Fantin; Patrícia Melchionna Albuquerque (Journal of Fungi, 2024)
Pigments of fungal origin have aroused increasing interest in the food dye and cosmetic industries since the global demand for natural dyes has grown. Endophytic microorganisms are a source of bioactive compounds, and Amazonian plant species can harbor fungi with a wide range of biotechnological applications. Popularly known in Brazil as crajiru, Fridericia chica is a medicinal plant that produces a red pigment. In this study, a total of 121 fungi were isolated in potato dextrose agar from three plants. We identified nine pigment-producing endophytic fungi isolated from branches and leaves of F. chica. The isolates that showed pigment production in solid media were molecularly identified via multilocus analysis as Aspergillus welwitschiae, A. sydowii, Curvularia sp., Diaporthe cerradensis (two strains), Hypoxylon investiens, Neoscytalidium sp. (two strains) and Penicillium rubens. These isolates were subjected to submerged fermentation in two culture media to obtain metabolic extracts. The extracts obtained were analyzed in terms of their absorbance between 400 and 700 nm. The pigmented extract produced by H. investiens in medium containing yeast extract showed maximum absorbance in the red absorption range (UA700 = 0.550) and significant antioxidant and antimicrobial activity. This isolate can thus be considered a new source of extracellular pigment.